The Principles of the Formation of the Environment of Pedestrian Spaces in the Context of Modern Urban Planning from the Standpoint of Sustainable Development. Issue 2 (February 2020) - Wagner, E; Avdeeva, E; Chernikova, K.
Abstract: Architectural environment of pedestrian spaces is the main platform from which a person perceives the urban space and interacts with it. A well-functioning system of pedestrian space is a multi-level structure efficiently organized at the local level, Integrated at the regional and Incorporated at the federal levels. Thus, the strategic policy in pedestrian space systems development shall rest on the hierarchic and multidimensional approach. On this basis we developed a multilevel system of construction principles for pedestrian spaces including basic and general principles as well as the system performance principles for any of the area planning levels. Continual quality improvement of the architectural environment of pedestrian spaces based on these principles implementation lets us develop the comfortable, safe, attractive and healthy urban environment decreasing time and material inputs both for current and future generations of its residents and brings along the sustainable development of the society and cities.